Employability and Communication Skills : Triangulating Views of Employers, Lecturers and Undergraduates - Teresa Wai See, Ong; Ting, Su Hie; Humaira, Raslie; Ernisa, Marzuki; Kee Man, Chuah; Collin, Jerome (2022)
Employability skills are known as soft skills and transferrable skills. Employability refers to skills, understandings, and personal attributes that increase graduates’ chances of employment and success in their chosen occupations (Yorke, 2004). Some of the skills listed under employability skills are resourcefulness, adaptability, and flexibility which are not only needed for adapting to work situations (Curtis & McKenzie, 2002). In a VUCA (volatility, uncertainty, complexity, and ambiguity) environment, there is a limit to what universities can equip graduates with, and they need to be able to continue learning to adjust to new situations and demands. According to the Secretary’s Commission on Achieving Necessary Skills (SCANS) in the USA (1992), employability skills can be divided into four clusters of basic skills, thinking skills, personal qualities, and workplace competence. These skills would give them an edge during interviews and increase their chances of getting employed. Malaysia has been experiencing graduate unemployability. Approximately 60% of graduates remain unemployed for minimum of a year after graduation (“Graduate Employability”, 2020). There are many factors that contribute to graduate unemployability such as lack of experience, language proficiency, communication skills, problem-solving skills, and critical thinking skills (Hanapi & Nordin, 2014; Lim et al., 2016; Nooriah & Zakiah, 2017; Ooi & Ting, 2017). Employers often specify good communication skills and interpersonal skills as top requirements in job advertisements (Bakar et al., 2007; Ooi & Ting, 2017). However, graduates lack problem solving skills, communication skills (Hanapi & Nordin, 2014) and technical knowledge (Lim et al., 2016). In a knowledge-based economy, employees need to be independent and self-motivated (Menand, 2014) to acquire the necessary knowledge, information and high skill levels to cope with the fast pace of technological change. There is currently scarcity of findings on whether universities and students are preparing themselves appropriately to meet the expectations of employers. The study investigated importance of employability and communication skills based on the views of employers, lecturers and students. The research questions were: (1) how good are university students in their employability and communication skills? and (2) do employers and lecturers agree on the most important skills an effective employee should have? The descriptive study involved the use of a questionnaire on employability skills and language skills (listening and speaking, reading and writing). The items were formulated using a five-point rating scale of (1) not at all, (2) to some extent, (3) just enough, (4) to a reasonable extent, and (5) to a great extent. In addition, the questionnaire required lecturers and employers to select the top 10 skills out of the 25 skills listed. The data were collected from 123 students, 26 lecturers from a public university, and 26 employers in Sarawak, East Malaysia. The students were mostly female (74.80% female, 25.20% male) and had weak to moderate language proficiency, measured using the Malaysian University English Test (MUET). There were slightly more males among lecturers (12 female, 14 male) and employers (11 female, 15 male). The average years of work experience for lecturers was 8.7 (range: 1-25) and for employers, the average was 5.6 (range: 1-15). For the analysis, means and frequencies were calculated for comparison of the three perspectives on the importance of communication and employability skills. The results showed that there was a difference among employers, lecturers, and students in their ratings of how good university students are in their employability and communication skills. The students overrated themselves in all three set of skills. Based on the mean scores, the students rated themselves as having a moderate level of employability (M=3.74), reading and writing skills (M=3.75), and listening and speaking skills (M=3.61). The lecturers rated the university students as having a moderate level of skills as well, but the mean scores were slightly lower than the students’ (employability, M= 3.54; reading and writing skills, M=3.49; listening and speaking skills, M=3.29). To the employers, only the fresh graduates’ listening and speaking skills were moderate but on the weak side (M=3.15). The employers found the fresh graduates’ reading and writing skills (M=2.97) and listening and speaking skills (M=2.92) to be slightly weak. Interestingly, the students and lecturers rated the graduates’ employability skills to be moderate but the employers considered them to be weak. Another contrast was the students’ listening and speaking skills, which the students and lecturers considered to be the lowest level, compared to employability and reading and writing skills. However, the employers considered the fresh graduates’ listening and speaking skills to be better than the other two skills. This comparison shows that there is a mismatch in the ratings of university students’ employability and communication skills given by employers, lecturers, and students. The employers’ expectation was higher than the lecturers’. In other words, most employers expect students to be ready to handle the demands of the workforce upon graduation but sadly, most graduates fell short of their expectations. The employers may feel that they have to spoon feed the graduates on various matters upon graduation and they prefer employees who have a strong set of communication and employability skills. Next, the results on the ranking of the important skills an effective employee should have also showed a mismatch in the perspectives of employers and lecturers. To the employers, the top two skills were time management and problem-solving aptitude, both of which were employability skills. To the lecturers, the top two skills were leadership qualities and teamwork spirit, which were also employability skills. The employers prioritised skills for efficient handling of work situations to meet deadlines but the lecturers focussed on skills for the completion of group work. The mismatch shows that lecturers and universities may have overlooked the need to train students to be versatile to solve problems and complete projects on time. Indeed, students often submit work late and are not independent enough to resolve questions concerning their projects on their own, and constantly have to consult lecturers. To increase graduate employability, universities need to collaborate strategically with the industry to resolve the mismatch of expectations, as other Malaysian studies have also found a mismatch (Nadarajah, 2021; Nesaratnam et al., 2020). However, because of the fast-changing work environment, students need to develop lifelong learning skills so that they can develop their expertise, knowledge base, and a lifelong learning mindset to stay relevant.